Bio-modification of sand for cement grouting - Ng, Samuel Joel Rui Ming (Nanyang Technological University, 2018)
Sand and aggregates used for concrete and grouting in Singapore are mainly imported from overseas. They are expensive and yet, the supplies are not sustainable. There is a need to look for ways to use less sand, less aggregates or substitutes for concrete and grouting, or use the same amount of sand or aggregates to produce higher strength concrete and grouting materials.